A Current Microbiological Picture of Mycobacterium Isolates from Istanbul, Turkey - SÜMBÜL, BİLGE; Doymaz, MZ; DOYMAZ, MEHMET ZIYA; Sumbul, BİLGE (My University, 2020)
Despite advances in diagnosis and treatment, tuberculosis (TB) continues to be one of the essential health problems throughout the world. Turkey is considered to be endemic for TB. In this study, we analyzed the distribution of Mycobacterium species, compare the diagnostic methods, and susceptibilities to anti-tuberculosis drugs of TB isolates. The aim was to document the current status and to provide a frame of reference for future studies. In this study, 278 Mycobacterium species isolated from 7,480 patients between September 2015 and June 2019 were included. Löwenstein-Jensen medium (LJ) and MGIT 960 were used for the isolation of strains. Susceptibility to 1st-line anti-tuberculosis drugs was determined. Positivity rates in clinical samples were as follows: 1.4% for direct microscopic acid-fast bacilli (AFB) detection, 3.4% for growth on the LJ, and 3.7% for growth on MGIT-960. Two hundred thirty-three isolates were identified as Mycobacterium tuberculosis complex (MTBC) and 45 were non-tuberculous mycobacteria (NTMs). Eleven of the NTMs (24.4%) were Mycobacterium fortuitum group isolates, and eight NTMs (17.7%) were Mycobacterium abscessus complex isolates. A number of patients diagnosed with tuberculosis peaked twice between the ages of 20–31 and 60–71. A hundred and eighty-two MTBC isolates (78.1%) were susceptible to all 1st-line anti-tuberculosis drugs, while 51 isolates (21.9%) were resistant to at least one drug tested. The multidrug-resistant tuberculosis rate was 13.7% among resistant strains and 3% in all strains. The liquid cultures were better for detection of both MTBC and NTMs isolates. The data demonstrate that MTBC continues to be challenge for this country and indicates the need for continued surveillance and full-spectrum services of mycobacteriology laboratory and infectious diseases.
Keywords: Mycobacterium